ANALISIS KADAR NITRAT DAN NITRIT AIR HUJAN YANG DITAMPUNG PADA CUBANG DI PULAU NUSA PENIDA KABUPATEN KLUNGKUNG - dhyana putri (Meditory : The Journal of Medical Laboratory, 2020)
The community water source in Nusa Penida Island is largely derived from rainwater that is collected in cubang used for drinking and clean water. This research aims were determine the levels of nitrate and nitrite in rainwater which is collected in cubang. The method used in this research is descriptive method. The examination was carried out using the spectrophotometric method. The results of examination of nitrate levels showed that 7 samples (23.3%) had nitrate levels above the maximum limit, while 23 samples (76.7%) had nitrate levels below the maximum limit, according to the regulation of Water Quality Standard I Pergub Bali No. 8 of 2007, which states that the maximum level of nitrate in water is 10 mg/L. The results of nitrite level examination showed 21 samples (70%) had nitrite levels above the maximum limit, while 9 samples (30%) had nitrite levels below the maximum limit, according to the regulation of Water Quality Standards I Pergub Bali No. 8 of 2007, which states that the maximum level of nitrite in water is 0.06 mg/L. The presence of nitrate and nitrite in rainwater are influenced by the nitrogen cycle that occurs in nature. The high levels of nitrate and nitrite in rainwater collected in cubang are supported by environmental conditions in the hole so that it makes it easier to contaminate.Keywords: rainwater, cubang, nitrate levels, nitrite levels